Sex Hormones Regulate SHANK Expression - Berkel, Simone; Eltokhi, Ahmed; Fröhlich, Henning; Porras-Gonzalez, Diana; Rafiullah, Rafiullah; Sprengel, Rolf; Rappold, Gudrun A. (Frontiers in Molecular Neuroscience, 2018)
Autism spectrum disorders (ASD) have a higher prevalence in male individuals compared to females, with a ratio of affected boys compared to girls of 4 : 1 for ASD and 11 : 1 for Asperger syndrome. Mutations in the SHANK genes (comprising SHANK1, SHANK2 and SHANK3), coding for postsynaptic scaffolding proteins, have been tightly associated with ASD. As early brain development is strongly influenced by sex hormones, we investigated the effect of dihydrotestosterone and 17β-estradiol on SHANK expression in a human neuroblastoma cell model. Both sex hormones had a significant impact on the expression of all three SHANK genes, which could be effectively blocked by androgen and estrogen receptor antagonists. In neuron-specific androgen receptor knock-out mice (ArNesCre), we found a nominal significant reduction of all Shank genes at postnatal day 7.5 in the cortex. In the developing cortex of wild-type CD1 mice, a sex-differential protein expression was identified for all Shanks at embryonic day 17.5 and postnatal day 7.5 with significantly higher protein levels in male compared to female pubs. Together, we could show that SHANK expression is influenced by sex hormones leading to a sex-differential expression, thus providing novel insights into the sex bias in ASD.